1995
DOI: 10.1016/s0960-9822(95)00181-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of gene expression in a complex differentiation hierarchy by global amplification of cDNA from single cells

Abstract: Tracking of sibling fates reliably identifies the differentiative potential of a single cell taken for PCR analysis, and demonstrates the existence of a variety of distinct and stable states of differentiative commitment. Global amplification of cDNA from single precursor cells, identified by sibling fates, yields a true representation of lineage- and stage-specific gene expression, as confirmed by hybridization to a broad panel of probes. The results provide the first expression mapping of these genes that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
144
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 163 publications
(146 citation statements)
references
References 63 publications
1
144
1
Order By: Relevance
“…Since Notch signalling is important in cell-fate decisions, it is important to determine the expression of the candidate genes in each ceIl population along the differentiation pathway. This goal was achieved by probing a lineage precursor blot (described in Brady et al, 1995; and in Section 2.7). The lineage precursor blot consists of amplified cDNAs from a hierarchy of hematopoietic precursor cells whose potential is known, from maturing hematopoietic cells, and three fibroblast cell lines.…”
Section: Notch In Hematopoiesismentioning
confidence: 99%
See 2 more Smart Citations
“…Since Notch signalling is important in cell-fate decisions, it is important to determine the expression of the candidate genes in each ceIl population along the differentiation pathway. This goal was achieved by probing a lineage precursor blot (described in Brady et al, 1995; and in Section 2.7). The lineage precursor blot consists of amplified cDNAs from a hierarchy of hematopoietic precursor cells whose potential is known, from maturing hematopoietic cells, and three fibroblast cell lines.…”
Section: Notch In Hematopoiesismentioning
confidence: 99%
“…The lineage precursor blot is a slot blot of amplified cDNAs made from precursors whose ceil fate is known, fiom maturing cells, and three fibroblast ce11 lines (Brady et al, 1995;described in more detail below). The library was constructed such that it consists of the most 3' untranslated region (3' UTR) of the genes expressed in a particular precursor.…”
Section: ' Untranslated Region Probesmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that UBE2H expression is up-regulated during differentiation of erythroblasts to reticulocytes and reduced during terminal differentiation stages (53,54). A similar expression pattern was described for Tal1, which is highly expressed in early erythrocyte stages and down-regulated during later stages of maturation (55,56). These observations may suggest a role of E2-conjugases and specifically UBE2H during late erythrocyte differentiation and a regulation by the hematopoietic transcription factor Tal1.…”
Section: Discussionmentioning
confidence: 52%
“…Then, the resultant cDNA solution was mixed with 11 ml of 2 Â tailing buffer containing 0.2 M potassium cacodylate (pH 7.2), 4 mM CoCl 2 , 0.4 mM dithiothreitol (DTT), 3.0 mM dATP, and 10 U of terminal transferase (Boeringer Manheim, Manheim, Germany), incubated at 371C for 15 min, and heated to 651C for 10 min. Aliquots (10 ml) of the above cDNA solutions were subjected to PCR in a 50-ml reaction solution containing a 3 0 -(dT) 24 -containing 60-base primer (KV-(dT) 24 primer: 5 0 -GGTAACTAATAC-GACTCACTATAGGGAGATGAATTC-(dT) 24 -3 0 ) as described by Brady et al 24,25 First-round PCR was performed for 25 cycles (941C for 1 min, 501C for 2 min, 721C for 6 min). After the firstround PCR, 1 ml of the first PCR product was added to 49 ml of the same PCR solution described above, and the second-round PCR was performed for 30 cycles (941C for 1 min, 501C for 1 min, 721C for 2 min).…”
Section: Construction Of Poly (mentioning
confidence: 99%